Validation of the inventory of Callous-Unemotional Traits among school-going adolescents in Malaysia. - Aref Ezrin Mohamad Khalil; Hue San Kuay; Maruzairi Husain; Yee Cheng Kueh (PLoS ONE, 2023)
A key component in the study of antisocial behaviour among adolescents is the presence of callous-unemotional (CU) traits. Among the established tools available to measure CU traits is the Inventory of Callous-Unemotional traits (ICU). To date, there is no validated questionnaire to assess CU traits for the local population. Therefore, there is a need to validate the Malay version of the ICU (M-ICU) so that research can be conducted to explore CU traits among adolescents in Malaysia. The aim of the study is to validate the M-ICU. Two phases of cross-sectional study involving 409 (phase 1 -exploratory factor analysis (EFA), n = 180; phase 2-confirmatory factor analysis (CFA), n = 229) adolescents aged between 13 to 18 years old were conducted from July until October 2020 at six secondary schools in Kuantan district. Participants were selected via multistage random sampling. The ICU was initially translated into Malay language using forward-backward translation procedure by a group of bilingual researchers. Study participants completed the final version of the M-ICU questionnaire and socio-demographic questionnaire. Data was analysed using SPSS version 26 and MPlus software for factor structure validity by performing EFA and CFA. Initial EFA revealed three factors with two items deleted. A further EFA with two factors resulted in the deletion of unemotional factor items. Cronbach's alpha for overall scale improved from 0.70 to 0.74. CFA supported a two-factor solution with 17 items compared to the original English version that has three factors with 24 items. The findings revealed acceptable fit indices (RMSEA = 0.057, CFI = 0.941, TLI = 0.932, WRMR = 0.968). The study revealed that a two-factor model with 17 items of the M-ICU has good psychometric properties. The scale is valid and reliable to measure CU traits among adolescents in Malaysia.